Medical innovation and its diffusion: Implications for economic performance and welfare - Frankovic, Ivan; Kuhn, Michael; Wrzaczek, Stefan (Journal of macroeconomics, 2020)
We study the impact on economic performance and welfare of medical innovations and their endogenous diffusion. We construct a general equilibrium model with a medical sector and overlapping generations subject to endogenous mortality and calibrate it to reflect the development of the US economy and health care over the cardiac revolution during the 1980s and 1990s. By counterfactual analysis we find that (i) medical innovations have increased welfare without compromising GDP growth; (ii) there is a sizeable welfare loss due to the adoption lag involved with imperfect diffusion; and (iii) there is scope for Pareto improvement by way of subsidization of innovative health care.